Host Jump of an Exotic Fish Rhabdovirus into a New Class of Animals Poses a Disease Threat to Amphibians - Eveline J. Emmenegger; Emma K. Bueren; Carla M. Conway; George E. Sanders; A. Noble Hendrix; Tamara Schroeder; Emiliano Di Cicco; Phuc H. Pham; John S. Lumsden; Sharon C. Clouthier (Viruses, 2024)
Spring viremia of carp virus (SVCV) is a rhabdovirus that primarily infects cyprinid finfishes and causes a disease notifiable to the World Organization for Animal Health. Amphibians, which are sympatric with cyprinids in freshwater ecosystems, are considered non-permissive hosts of rhabdoviruses. The potential host range expansion of SVCV in an atypical host species was evaluated by testing the susceptibility of amphibians native to the Pacific Northwest. Larval long-toed salamanders Ambystoma macrodactylum and Pacific tree frog Pseudacris regilla tadpoles were exposed to SVCV strains from genotypes Ia, Ib, Ic, or Id by either intraperitoneal injection, immersion, or cohabitation with virus-infected koi Cyprinus rubrofuscus. Cumulative mortality was 100% for salamanders injected with SVCV, 98–100% for tadpoles exposed to virus via immersion, and 0–100% for tadpoles cohabited with SVCV-infected koi. Many of the animals that died exhibited clinical signs of disease and SVCV RNA was found by in situ hybridization in tissue sections of immersion-exposed tadpoles, particularly in the cells of the gastrointestinal tract and liver. SVCV was also detected by plaque assay and RT-qPCR testing in both amphibian species regardless of the virus exposure method, and viable virus was detected up to 28 days after initial exposure. Recovery of infectious virus from naïve tadpoles cohabited with SVCV-infected koi further demonstrated that SVCV transmission can occur between classes of ectothermic vertebrates. Collectively, these results indicated that SVCV, a fish rhabdovirus, can be transmitted to and cause lethal disease in two amphibian species. Therefore, members of all five of the major vertebrate groups (mammals, birds, reptiles, fish, and amphibians) appear to be vulnerable to rhabdovirus infections. Future research studying potential spillover and spillback infections of aquatic rhabdoviruses between foreign and domestic amphibian and fish species will provide insights into the stressors driving novel interclass virus transmission events.